POLA KOMUNIKASI ANTARBUDAYA PASANGAN SUAMI-ISTRI BEDA SUKU (Antara Suku Pekal Dengan Suku Jawa Di Bengkulu Utara) - Alen Manggola (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACTThis type of research is qualitative using field research methods. Data collection techniques in this study are through interviews, observation, and documentation. The data analysis techniques use inductive and descriptive forms of narrative. The results showed that communication problems in inter-ethnic couples between the Pekal and Javanese tribes could be motivated by a lack of understanding of the partner's language, as well as cultural differences. The solution in dealing with the communication problem of inter-ethnic couples between the Pekal and Javanese tribes is to use a language that can be understood by both parties, namely Indonesian. The results of the presentation to couples about the myth of the prohibition of inter-ethnic marriage between the Pekal and Javanese tribes received a positive response so that it did not cause problems for the marriage, but some were anxious or worried. The reason for the new culture can arise from the existence of marriages with different ethnic groups between the Pekal and Javanese tribes, namely because of the new environment, new habits, and the mixing of the two cultures brought by each partner. Keyword: communication, intercultural, husband and wife